2004
DOI: 10.1063/1.1809115
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous nucleation rates of 1-pentanol

Abstract: We have measured isothermal homogeneous nucleation rates J for 1-pentanol vapor in two different carrier-gases, argon, and helium, using a two-valve nucleation pulse chamber. The nucleation rates cover a range of 10(5) Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 31 publications
5
37
0
Order By: Relevance
“…44 While the standard CNT typically predicts the correct dependence of nucleation rates on supersaturation, it gives the wrong temperature-dependence. For substances such as water and 1-pentanol, this has been well documented, 1,7,45 and it is also evident from comparing the red dashed lines in Fig. 2 with the experimental results.…”
supporting
confidence: 53%
“…44 While the standard CNT typically predicts the correct dependence of nucleation rates on supersaturation, it gives the wrong temperature-dependence. For substances such as water and 1-pentanol, this has been well documented, 1,7,45 and it is also evident from comparing the red dashed lines in Fig. 2 with the experimental results.…”
supporting
confidence: 53%
“…Their data are depicted together with our simulation data in Fig. 7 From this figure, an interesting coincidence between our simulation results and the experimental data of Iland et al 1 and Hruby et al 10 can be noticed, i.e., a very good agreement of the slope, but a near-constant shift to larger differences from CNT for the simulation data when the B͑T͒ effect is included. 1 Although the experimental results ͑using various techniques͒ coincide at 260 K, the temperature dependence of the nucleation rate ratio is rather inconsistent.…”
Section: Resultssupporting
confidence: 83%
“…6 in Ref. 1 Although the experimental results ͑using various techniques͒ coincide at 260 K, the temperature dependence of the nucleation rate ratio is rather inconsistent. Their data are depicted together with our simulation data in Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The effect of the amount and type of carrier gas has been investigated in the past in experiments and simulation. In experimental work on 1-pentanol gas-liquid nucleation using an expansion chamber, no influence of the choice of the two different types of carrier gases argon and helium has been found (48). On the other hand, Brus et al (49) have investigated the nucleation of 1-pentanol in a laminar flow diffusion chamber and found that the nucleation rates in argon are shifted to lower supersaturations than in helium.…”
Section: Methodsmentioning
confidence: 98%